THE RELATIONSHIP BETWEEN ABDOMINAL MUSCLE STRENGTH AND LIMB MUSCLE EXPLOSIVENESS TO THE SMASH ABILITY OF VOLLEYBALL UNIT MEMBERS MUHAMMADIYAH UNIVERSITY OF SURAKARTA - Aditya Bagas Pratama; Vera Septi Sistiasih (Yayasan Education and Social Center, 2021)
This study aims to determine the relationship between abdominal muscle strength and leg muscle explosive power with volleyball smash ability. The population in this study was all 20 members of the volleyball unit UMS who found 20 people. The data was collected using the sit-up test to measure the strength of the strength and the vertical jump test to measure the explosive power of the leg muscles, performing the smash accuracy test 3 times in a row. The results of data analysis show that:(1) Abdominal muscle strength has a relationship with smash ability of 0.855 and r_count (20; 0.05) = 0.456 while r_count (20; 0.01) = 0.575 it can be concluded that the correlation ability of 58.5%. (2) abdominal muscle strength has a relationship with the ability to smash, the value of r_count is 0.366 and r_count (20 ; 0.05) is0.456 while r_count (20 ; 0.01) is 0.575. it can be concluded that the correlation coefficient is 36.6% (3) abdominal muscle strength and leg explosive power have a relationship with volleyball smash ability, the value of r_count is 0.462 and r_count (20; 0.05) is 0.456 while r_count (20;0.01) is 0.575. it can be concluded that the correlation coefficient is significant at 45.6%